Приведите формулу ¬((y⇒¬x)⇔y) к к.н.ф. или д.н.ф методом равносильных преобразований.

Girlverysilly098887 Girlverysilly098887    1   02.07.2020 16:52    3

Ответы
nastycherry1 nastycherry1  15.10.2020 15:10

\neg ((y \to \neg x) \leftrightarrow y) = \neg ((\neg y \vee \neg x) \leftrightarrow y) = \neg ((\neg y \vee \neg x) \wedge y \vee \neg (\neg y \vee \neg x) \wedge \neg y) = \\\\= \neg ((\neg y \vee \neg x) \wedge y \vee y \wedge x \wedge \neg y) = \neg ((\neg y \vee \neg x) \wedge y \vee 0) = \neg (( y \wedge \neg y) \vee (y \wedge \neg x)) =\\\\= \neg (0 \vee y \wedge \neg x) = \neg (y \wedge \neg x) = \neg y \vee x

Получили КНФ: \neg y \vee x

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика